DIAPHRAGMATIC HERNIA OF GRAVID UTERUS AND RIGHT SIDED DISPLACEMENT OF HEART IN A DOMESTIC SHORT-HAIRED CAT - D. Nak; N. Celımlı; E. Karakaya; H. Kurt; A. H. Shahzad; M. Akbala; B. Guner (Journal of Animal and Plant Sciences, 2016)
Present case report is about very rare condition of gravid uterus herniation into the thoracic cavity and right sided heart displacment in a  three year old queen. Cat was presented to obstetrics and gynecology clinic with a history of overdue kittening date. Abdominal cavity was found to have an unusual solid mass in cranial part with little fluid oozing from vulva. Roentgenogram assesment revealed a fetus skeleton in abdomen with two similar skeletons in thoracic cavity and missing a normal diaphragmatic line. Similar findings were recorded on ultrasonography. Midline coeliotomy was done under general gas anesthesia. Diaphragmatic wall had 6 cm left–sided vertically oriented rent in the dorsal aspect with gravid uterine and a 2 cm right-sided vertically oriented in the middle of the diaphragm with liver lobe and gall bladder herniation. Three partially mummified fetuses were recovered. Both diaphragmatic tears were reduced and cat was neutered to avoid future complication. According to available data this is first atypical report in pet practice particularly in feline.
Keywords: Gravid uterus; Thoracic cavity; Diaphragmatic herniation; Short haired cat; Displaced heart; right sided; Fetuses